THE CORRELATION BETWEEN INTERPERSONAL INTELLIGENCE AND STUDENTS’ READING COMPREHENSION - Muhammad Khusairi Nasution; Eka Wilany (English Department, University of Riau Kepulauan, Batam,Indonesia, 2020)
The purpose of this study was to find out whether there is a correlation between students 'interpersonal intelligence and students' reading comprehension. The research design used in this research was quantitative correlational research. The populations in this study were 40 students of fourth semester at English Department in Academic Year 2019/2020. The population was selected by simple random sampling technique. The sample in this research was 29 students. Interpersonal Intelligence Questionnaire and Reading Comprehension Test were used as instruments of this study after the validity and reliability tests of the two instruments were conducted. The data normality test used in this study was Kolmogorov Smirnov. The researcher analyzed the correlation using the Pearson Product Moment formula to find out correlation between Students’ Interpersonal Intelligence and Students’ Reading Comprehension. The research found out that there was a significant correlation between Students' Interpersonal Intelligence and Students' Reading Comprehension of fourth semester at English department Universitas Riau Kepulauan in Academic Year 2019/2020. Suggestions were taken by researcher, namely that teachers must be aware of the importance of interpersonal intelligence in students to assist students in honing students 'interpersonal intelligence and students must realize and hone interpersonal intelligence that is in themselves.